Targeted metabolomics analysis of aromatic amino acids and their gut microbiota–host cometabolites in rat serum and urine by liquid chromatography coupled with tandem mass spectrometry. Issue 16 (31st July 2017) - Zeng, Yifeng; Luo, Liang; Hou, Waner; Lu, Biyu; Gong, Jing; Chen, Jiahui; Zhang, Xiaojun; Han, Bo; Xie, Zhiyong; Liao, Qiongfeng
Abstract : Gut microbiota–host cometabolites are closely related to various diseases. Monitoring dynamic changes of cometabolites can provide a more comprehensive understanding of pathophysiology. Here, a novel liquid chromatography–tandem mass spectrometry method was performed for the analysis of aromatic amino acids and their gut microbiota–host cometabolites in rat serum and urine. In the developed method, seven key gut microbiota–host cometabolites were chromatographically separated on a Kinetex Phenyl‐Hexyl column by gradient elution, and the run time was 6 min. Serum and urine were extracted by protein precipitation. This method was linear between 10.20 and 1000.00 ng/mL for phenylalanine and p ‐cresyl sulfate; 25.60–2500.00 ng/mL for tryptophan; 51.20–5000.00 ng/mL for tyrosine, indole, and indoxyl sulfate; and 75.50–7500.00 ng/mL for p ‐cresol. The linearity, accuracy, precision, and recovery of seven analytes were all satisfactory. The method was sufficiently sensitive and robust. It was successfully applied to characterize the alterations of gut microbiota–host cometabolites in inflammatory disorders. All of these results suggest that the developed method is able to simultaneously monitor aromatic amino acids and their gut microbiota–host cometabolites. This method will be expected to be a valuable tool for clinical researches and comprehensive studies of the pathophysiological roles.